Anticoncepção pela lactação com amenorréia : conhecimento e prática de enfermeiros - Freitas, Giselle Lima de (2009)
Exclusive to The Lactation Amenorrhea (LAM) is a contraceptive method (MAC) natural, with efficiency of 98% by the sixth month of life. Currently, promotion of MAC is available in the country carried out by teams of the Family Health Program (FHP), particularly by nurses, who must do it in neutral, respecting the free choice of users. The aim of this study was to analyze knowledge and performance of nurses of the PSF on the LAM. The specific objectives were: To identify personal experiences of nurses (parents or mothers) in relation to breastfeeding and LAM; To assess knowledge and confidence of nurses related to LAM; To identify promotion of LAM by the perception of nurses and how the acceptance of LAM by the customer; To know opportunities and strategies used by nurses to promote LAM; To show results of the practice of nurses with respect to the monitoring of users of LAM. It was a field study, cross, held from February to July 2008, the Regional Executive Secretariats (SER) I, III, IV and V of Fortaleza-CE, with 137 nurses. Data collection occurred in the Basic Health Units using the interview. There were the nurses, accounting for 121 (88.3%) participants, who had a mean age of 35.1 years. Slightly more than half, 70 (51.1%) reported having children, and of those, 61 (92.4%) reported having experienced exclusive breastfeeding, which had an average of 4.38 months. However, only 12 (19.6%) nurses said they had adopted the LAM, even considering its practicality and its benefits. Only 2 (1.5%) nurses know how to LAM contraceptive option. As the self-assessment of knowledge on the subject, 34 (24.8%) nurses rated their knowledge as excellent or good, 80 (58.4%) good, 20 (14.6%) as regular and 3 (2, 2%) inadequate. Most, 88 (64.2%), know the effectiveness of LAM and only 5 (3.7%) reported the efficacy correct. Even with 65 (47.4%) of nurses discrediting the effectiveness of LAM and only 19 (13.9%) being knowledgeable of the three requirements for optimal operation of the method, 112 (81.8%) said guide for women on the use of it. The acceptance of women occurs in part, to the extent that seeking complementary method to continue use of LAM. The guidance is provided by nurses at different times, related to the pregnancy-puerperal period (prenatal, postpartum and child care) and outside, in the consultations for family planning and, in most cases, adopted the individual approach. The students, 59 (52.7%) nurses accompanied users of LAM. The average time of use by customers is 3 to 4 months, and the return to work and the introduction of other foods to the infant diet the main reasons for discontinuation of LAM. The oral combination was the MAC of succession of LAM. It is therefore the need to improve knowledge of nurses of the PSF over the area of care, since in such circumstances the promotion of LAM is compromised, affecting the adherence of women to the method and the effectiveness of it.